Upaya Petani Sawit Dalam Meningkatkan Perekonomian Berdasarkan Perspektif Ekonomi Islam Di Desa Sungai Sayang - Hamzah, Ferdi -; Mustofa, Muhammad Arif; -, Nurjali - (Jurnal Ilmiah Ekonomi Islam, 2023)
The development of the agricultural sector is still an important sector in encouraging the acceleration of regional development For Jambi province,. This can be seen from the still large contribution of the agricultural sector to GRDP and labor absorption for the economy of the Jambi province region. The agricultural sector has contributed around 27.5% to the GRDP of Jambi province and has also been able to absorb a relatively large number of workers, namely 46.88% of the existing workforce.. The aim of this research is to find out how palm oil farmers are making efforts to improve the economy in Sungai Sayang Village and to find out how palm oil farmers are making efforts to improve the economy based on an Islamic economic perspective in Sungai Sayang Village. In this study the authors used a qualitative approach with descriptive analysis method. The results of this research are that people get permanent jobs and income and people get additional income. The community is able to send their children to a higher level. The community is able to help others by hiring workers. The community at work has 3 things that must be implied, namely hard work, smart work and sincere work.